Combining Quantum Dot and Perovskite Photovoltaic Cells for Efficient Photon to Electricity Conversion in Energy Storage Devices. Issue 10 (6th September 2022) - Johansson, Erik M. J.; Andruszkiewicz, Aneta
Abstract : Renewable energy sources, such as wind and solar power, are increasingly important today to reduce emissions from fossil‐based energy sources. However, the electricity from wind and solar power varies over time and depends on weather conditions and the time of the day. Therefore, to include a large fraction of electricity from these energy sources in the electricity grid, large‐scale and low‐cost energy storage is needed. Herein, it is investigated how a combination of quantum dot based photovoltaic cells and perovskite‐based photovoltaic cells can be used to increase the energy conversion efficiency and increase the working range of energy storage devices based on conversion between heat, light, and electricity. The results show that these new types of photovoltaic materials have very promising properties for efficient utilization in energy storage devices, which have the potential for large‐scale and low‐cost energy storage. Abstract : A combination of perovskite and quantum dot photovoltaic cells are used for the conversion of heat radiation to electricity. The combined photovoltaic cells convert photons in a broad energy range to electricity, which may be interesting for utilization in electricity storage systems based on conversion of heat and electricity.